The Psychospiritual Function of Shalat Dhuha in Reducing Academic Anxiety among University Students: A Phenomenological Study - Khaira, Rizki; Yati, Abizal M.; Duri, Rofiqa (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2023)
This qualitative study explores the function of Shalat Dhuha (mid-morning prayer) in reducing anxiety among final-year students in the Islamic Guidance and Counseling Program. The phenomenon of academic anxiety, intensified by thesis-related pressure and social expectations, was examined through a phenomenological approach to capture students’ lived spiritual and psychological experiences. Data were collected through semi-structured interviews, participatory observations, and reflective documentation, involving six purposively selected participants. Thematic analysis identified three main forms of anxiety, psychological, physiological, and socio-moral, each interlinked within students’ academic and spiritual lives. Findings revealed that consistent performance of Shalat Dhuha fosters emotional balance, self-regulation, and spiritual awareness, functioning as an effective religious coping mechanism. The prayer cultivates calmness, gratitude, and tawakkul (trustful surrender), aligning with the principles of Islamic psychology and mindfulness-based therapy. The study contributes to the theoretical development of Islamic Guidance and Counseling, bridging spiritual practice with modern psychological frameworks. Practically, it proposes the integration of structured Shalat Dhuha-based counseling within higher education as a holistic model for addressing student anxiety and enhancing well-being.